Hi there,
Can anyone offer some advice on how one would go about solving this equation? I can't figure it out!
(x+2)(y+2)+(x-3)(y+2)=0
Thanks in advance,
Josh
$\displaystyle (x+2)(y+2) + (x-3)(y+2) = 0 $ only when $\displaystyle (x+2)(y+2) = 0 $ and $\displaystyle (x-3)(y+2) = 0 $
$\displaystyle (x+2)(y+2) = 0 $ when x = -2 or y = -2
$\displaystyle (x-3)(y+2) = 0 $ when x = 3 or y = -2
y=-2 is the only one which makes both eqn 0, so y = -2 is the soln.
Hi Dave,
Thanks for your reply.
That makes sense but I'm wondering if there's an algebraic methodology I can use? I know that the other solution is x=0.5, so can I do the following:
Ignore (y+2) and (y+2) so you have
X + 2 + x - 3
= 2x -1
X = -0.5
This comes out, but doesn't seem like its the correct way to go about it!